Novel Nano-Fe2O3-Co3O4 Modified Dolomite and Its Use as Highly Efficient Catalyst in the Ozonation of Ammonium Solution. (1st August 2020) - Nguyen, Manh B.; Le, Giang H.; Pham, Trang T. T.; Pham, Giang T. T.; Quan, Trang T. T.; Nguyen, Trinh Duy; Vu, Tuan A.
Abstract : Catalytic ozonation is a new method used for removal of NH4 OH solution. Therefore, high catalytic performance (activity and selectivity) should be achieved. In this work, we report the synthesis and catalytic performance of Fe2 O3 -Co3 O4 modified dolomite in the catalytic ozonation of NH4 OH solution. Dolomite was successfully activated and modified with Fe2 O3 and Co3 O4 . Firstly, dolomite was activated by heating at 800°C for 3 h and followed by KOH treatment. Activated dolomite was modified with Fe2 O3 by the atomic implantation method using FeCl3 as Fe source. Fe2 O3 modified dolomite was further modified with Co3 O4 by precipitation method. The obtained catalysts were characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), energy-dispersive X-ray spectroscopy (EDS), scanning electron microscopy (SEM), N2 adsorption–desorption (BET), and temperature-programmed reduction (H2 -TPR). From SEM image, it was revealed that nano-Fe2 O3 and Co3 O4 particles with the size of 80–120 nm. Catalytic performance of activated dolomite, Fe2 O3 modified dolomite, and Fe2 O3 -Co3 O4 modified dolomite in catalytic ozonation of NH4 + solution was investigated and evaluated. Among 3 tested catalysts, Fe2 O3 -Co3 O4 modified dolomite has the highest NH4 + conversion (96%) and N2 selectivity (77.82%). Selectivity toward N2 over the catalyst was explained on the basis of bond strength M-O in oxides through the standard enthalpy Δ H ° f of oxide. Catalyst with lower Δ H ° f value has higher N2 selectivity and the order is the following: Co3 O4 (Δ H ° f of 60 kcal (mole O)) > Fe2 O3 (Δ H ° f of 70 kcal (mole O)) > MgO (Δ H ° f of 170 kcal (mole O)). Moreover, high reduction ability of Fe2 O3 -Co3 O4 modified dolomite could improve the N2 selectivity by the reduction of NO3 - to N2 gas.